1972-1973 ネン, ナンキョクカイ インドヨウ ク ニ オケル クロロフィルα ノ スイチョク ブンプ - 黒田, 一紀; クロダ, カズノリ; 福地, 光男; フクチ, ミツオ; Kuroda, Kazunori; Fukuchi, Mitsuo (1982)
P(論文) 第14次日本南極地域観測隊の海洋生物調査の一環として, 南極海インド洋区において, 水深500mまでのクロロフィルα量の垂直分布を調査した。観測は, 1972年12月に「ふじ」南下航路上の東経105度線に沿った南緯38～60度間の6点, および南緯60度以南域の2点で行われた。1973年2～3月の北上航路上においては東経15度線上に沿った南緯67～35度間の9点で観測を実施した。表面海水中および亜表層極大層におけるクロロフィルα量は, 南下航路上の南極海域において顕著に高かった。全観測点を通して, 0～250m水柱内のクロロフィルα積算値は17～129mg/m^2であり, 特に南下航路上の南極海域において高かった。これは12月下旬が南極海域における植物プランクトンの増殖期に相当することによる現象と考えられた。有光層内のクロロフィルα積算値は8～43mg/m^2であった。有光層より下層における高クロロフィルα量分布が, 南極海域において顕著にみられた。表面海水中のクロロフィルα量と亜表層におけるクロロフィルα量およびクロロフィルα積算値との間に正の相関がみられた。 In the Indian sector of the Antarctic Ocean, vertical distribution of chlorophyll a down to a depth of 500m was investigated. The observations were carried out as part of the marine biological programs of the 14th Japanese Antarctic Research Expedition at six stations on the southward leg of the FUJI between 38°and 60°S along 105°E, two stations south of 60°S in December 1972,and at nine stations on the northward leg between 67°and 35°S along 15°E in February and March 1973. High surface chlorophyll a contents and the remarkable subsurface maximum of chlorophyll a were distributed in the Antarctic water on the southward leg. Integrated chlorophyll a stocks in a 0-250m water column were in the range of 17-129mg/m^2 and high values were found in the Antarctic water on the southward leg. The enhancement of chlorophyll a in late December seems to coincide with the blooming season of phytoplankton in the Antarctic water. The integrated stocks of chlorophyll a in the euphotic zone were in the range of 8-43mg/m^2. A large amount of chlorophyll a contents below the euphotic zone were distributed mainly in the Antarctic water. Positive correlations among surface chlorophyll a contents, subsurface chlorophyll a contents and integrated chlorophyll a stocks were found. departmental bulletin paper